Hydroperoxides can modulate the redox state of pyridine nucleotides and the calcium balance in rat liver mitochondria - Lötscher, Hans Ruedi (1979)
When rats are fed a selenium-deficient diet, the glutathione peroxidase activity in liver mitochondria decreases within 5 weeks to 0-6% of that of control animals fed on a diet supplemented with 0.5 ppm of selenium as sodium selenite. Analysis of the temperature dependence of energy-linked Ca(2+) uptake by means of Arrhenius plots reveals two breaks (at around 11°C and 24°C) in mitochondria isolated from selenium-supplemented animals, whereas in selenium-deficient rats the break at 11°C is absent. Ca(2+)-loaded mitochondria of selenium-supplemented rats—i.e., with active glutathione peroxidase in the matrix—lose Ca(2+) rapidly, with a concomitant oxidation of endogenous NAD(P)H, when exposed to t-butyl hydroperoxide or H(2)O(2). In contrast, in selenium deficiency, t-butyl hydroperoxide and H(2)O(2) induce neither a release of Ca(2+) nor an oxidation of NAD(P)H. The peroxide-induced oxidation of NAD(P)H is reversible in the presence of succinate when no Ca(2+) has been taken up. When Ca(2+) has previously been accumulated, however, the oxidation of NAD(P)H is irreversible. Enzymatic analysis of mitochondrial pyridine nucleotides reveals that the peroxide-induced oxidation of NAD(P)H in Ca(2+)-loaded mitochondria leads to a loss of NAD(+) and NADP(+). It is proposed that the redox state of mitochondrial pyridine nucleotides can be or is in part controlled by glutathione peroxidase and glutathione reductase and is a factor in the balance of Ca(2+) between mitochondria and medium.